Analysis of Mathematics Learning Management at Madrasah Tsanawiyah Integrated with Ethnomathematics - Pujiani, Sri; Aswasulasikin, Aswasulasikin; Yakin, Ilmanul (Sumber Belajar Sejahtera, 2025)
This study aims to determine the quality of mathematics learning management at the Madrasah Tsanawiyah level, integrated with Ethnomathematics, covering the planning, implementation, and evaluation conducted by mathematics teachers. The research was conducted at MTs Negeri 1 Lombok Timur in grades VII, VIII, and IX using a descriptive qualitative approach. Data collection was carried out in a natural setting using various techniques, including observation, interviews, document studies, and data triangulation to ensure the validity, credibility, and consistency of the research data. The methods used involved participant observation, in-depth interviews, and documentation. The findings of the study include: (1) Teachers have a good understanding of the curriculum and its development. (2) Teachers demonstrate competence in managing mathematics learning integrated with Ethnomathematics. (3) Challenges exist in managing mathematics learning when linked to Ethnomathematics. This study discusses the management of Mathematics Learning Integrated with Ethnomathematics at Madrasah Tsanawiyah, focusing on learning management, teacher understanding, and classroom implementation. The results indicate that although all teachers understand the curriculum, only 57.14% have an in-depth understanding of Ethnomathematics. While most teachers emphasize lesson planning (85.7%), only 28.57% apply Ethnomathematics-based learning models. The main challenges include limited teacher understanding, time constraints, and low student readiness. Efforts made to address these challenges include lecture and discussion methods, as well as the integration of Ethnomathematics in learning. However, the application of Ethnomathematics still requires improvement through further training and support to be effectively implemented and to contribute to the preservation of local culture.